Moral Reasoning As A Factor To Prevent Academic Fraud In Health Students - Aria Daniswara; Naufal Aldian Pratama; Yanti Cahyati (Media Informasi, 2026)
Academic fraud remains a significant issue in higher education, including among health students who are expected to uphold strong ethical and professional standards. This study aimed to examine the role of moral reasoning as an internal factor in preventing academic fraud within health education. The review was guided by theoretical frameworks including Kohlberg’s theory of moral development and the Fraud Triangle/Diamond models to interpret the interaction between internal and external determinants of academic fraud. The analysis shows a consistent negative relationship between moral reasoning and academic fraud, indicating that health students with higher moral reasoning demonstrate stronger ethical reflection and lower tendencies toward dishonest academic behaviors, even under academic pressure. However, external factors such as permissive academic environments and increased access to technology, including generative AI, may reduceth protective effect. Therefore, strengthening moral reasoning through structured ethics education, reflective learning, and curriculum integration is essential as a long-term strategy to prevent academic fraud and to foster ethical integrity among future healthcare professionals